RHG gets green stamp. (Bookseller, 2006)
This article reports that Random House Group Ltd. (RHG) has been awarded the Forest Stewardship Council (FSC) Chain of Custody status, which enables it to carry the FSC logo on books. The FSC tracks timber from tree to end product, and ensures it is from environmentally and socially responsible sources. RHG is the first consumer publishing group to be awarded the certification, although titles from other publishers may bear the logo where it has been licensed to the printer. The move was part of a procurement policy set out by the group last year, alongside similar commitments by HarperCollins Publishers Inc., Egmont and Pearson.